Uji Antagonis Bakteri Simbion Spons dari Pulau Bakar terhadap Jamur Candida Albicans - Rizki Amelia Nasution; Ulfayani Mayasari (Biotropic : The Journal of Tropical Biology, 2022)
Sponge symbiont bacteria are microbes that live in marine sponges and are known to have bioactive compounds with antimicrobial propeties. Sea sponges on Bakar Island are known to contain many types of symbiotic bacteria. This study was conducted to test the ability of the sponge symbiont bacteria to inhibit the growth of the fungus Candida albicans. The study was carried out in 3 stages, with were sample collection, isolation and antifungal activity test using the well diffusion technique. Sponge symbiont bacteria were obtained as many as 16 isolates and were successfully tested for as many as 11 isolates for their antifungal abilities. Of the 11 isolates, based on the characteristics tested, 1 isolate (SPS4F2) was obtained with strong criteria (12.06 mm) and 10 (SPS1, SPS3, SPS5, SPS6, SPS7 SPS8, SPS9, SPS10, SPS11, SPS12, SPS13) others with moderate criteria (±6.00-9.00). The results of the study can be concluded that the sponge symbiont bacteria from Bakar’s Island mostly have the potential as antifungals against Candida albicans and based of characterization including the Bacillus.